Estudio de factibilidad para la creación de un programa de formación empresarial para emprendedores en el cantón Quevedo año 2015 - Giler Burgos, Alba Monserrate (2015)
In Quevedo Canton and its surrounding areas, both in the province of Los Rios, there are few consulting firms that provide training services but focused on the education sector, so the present feasibility study it conducted to determine the feasibility of an entrepreneurial center, for which the needs of this sector were analyzed regarding training services aimed at people who play various business positions. To implement the feasibility study, various techniques and research instruments were used, which made possible the collection, interpretation and analysis of the results achieved through the application of surveys and interviews, respectively workers, administrators, department heads and managers of companies in the business sector Quevedo Canton and the surrounding areas. The results of the study, answer the questions allowed, achieve the objectives, which led to capture the respective conclusions and recommendations. Through analysis, it was verified that there is clearly a high degree of acceptance of a training center that offers its services according to the needs of industry in the canton Quevedo, it was found that there is little training enterprises in the area, these offered a limited training and poor service, this is the product of dissatisfaction, which makes possible the establishment of a center of entrepreneurship in the sector. With products obtained from market research it determined that there is the feasibility of implementing efficient advertising strategies to position the training center.